A tipologia moral na filosofia de Nietzsche - Souza, Israel Fabiano Pereira de (Universidade Federal de São Carlos, 2019)
This study is an attempt to understand the importance of developing a typology within the moral reflections proposed by Nietzsche. We understand that typological analysis is primarily a way of moving away from metaphysical thinking, as well as from an absolute generalization of concepts and values held by universals. Moreover, moral types are, we believe, in line with the Nietzschean view of reality, which is characterized by a plurality of meanings and values, which are embedded in a constant becoming and do not allow the existence of the axiological and conceptual crystallization desired by metaphysics. This view fits in with the Nietzschean concepts of will to power and perspectivism that we believe are fundamental to understanding why Nietzsche points to the need to erect a moral typology. Finally, we must think of moral typology as the product of genealogical research. It is from moral genealogy that we gain insight into values and morals through their importance or harm to life. Types in this context are expressions of a certain form of life, whether ascending or degenerate.
The moral typology in nietzsche's philosophy
Die moralische Typologie in Nietzsches Philosophie
Keywords: Tipologia; Genealogia; Metafísica; Perspectivismo; Vontade de poder; Nietzsche; CIENCIAS HUMANAS::FILOSOFIA::ETICA